Análise modal como ferramenta de análise de segurança estática de tensão em sistemas de potência - Weigert, Gabriela Rosalee (2021)
Static voltage security assessment in electric power systems comprises stability analysis of the operation point, as well as contingency analysis and the proposition of control strategies. In order to perform contingency analysis, the selected contingencies must be screened and ranked. Contingency evaluation is executed in real-time, thus it is essential to reduce the computational cost of this part of the analysis. Therefore, the stages of contingency screening and ranking must be effective, in order to assure that the simulations involving more complete models are executed only for the most critical cases. One of the most frequent indices that measure voltage instability is the voltage stability margin. Still, most of the contingency ranking methods in literature (L, FVSI, PI) are not based on this indicator, yet are formulated on simpler grounds. Therefore, traditional ranking methods do not necessarily attest about the proximity of each contingency to instability, as does voltage stability margin. In addition, contingency ranking indices are not useful to determine control strategies. Thus, it is necessary to perform complementary analysis in order to suggest control strategies in a traditional contingency analysis method. In this manner, this work proposes a new method to be integrated to the process of static voltage security assessment. A method of contingency screening and ranking is proposed, as well as an analysis of control strategies method. Both tools rely on the modal analysis of the power flow equation’s jacobian matrix. The goal of the proposed screening and ranking algorithm is to indicate the contingency associated with the most critical voltage stability margin. The indices obtained in the contingency analysis stage are kept and reused in the analysis of preventive and emergency control strategies, in order to drive the system to a secure state, or the closer it can get to a secure state. Preventive control strategies are proposed for the complete system, respecting operational limits, while emergency control strategies, to be implemented in a postcontingency situation, are proposed for the contingencies that violate security constraints. The proposed methodology was simulated on IEEE 14, 30 and 57 buses test-systems. The precision of the ranking algorithm was satisfying if compared with literature methods and with voltage stability margin based ranking. Control strategies propositions are presented for the 57 buses system. Even though there were no comparisons with literature control preposition methods, the performance of the proposed algorithm is commented.